Algunas regularidades en la ontogénesis de la sintaxis búlgara - Popova, V. (Eslavística Complutense, 2003)
The aim of the suggested research is to highlight the basics in the ontogenesis of Bulgarian syntax. A functional analysis is made of empirical data drawn from a longitudional observation of four Bulgarian children aged between one and six years.